Therapeutic potential of matrix metalloproteinases in Duchenne muscular dystrophy - Ogura, Yuji; Tajrishi, Marjan M.; Sato, Shuichi; Hindi, Sajedah M.; Kumar, Ashok (Frontiers in Cell and Developmental Biology, 2014)
Matrix metalloproteinases (MMPs) are secreted proteinases that have physiologic roles in degradation and remodeling of extracellular matrix (ECM) in almost all tissues. However, their excessive production in disease conditions leads to many pathological features including tissue breakdown, inflammation, cell death, and fibrosis. Duchenne Muscular dystrophy (DMD) is a devastating genetic muscle disorder caused by partial or complete loss of cytoskeletal protein dystrophin. Progressive muscle wasting in DMD is accompanied by myofiber necrosis followed by cycles of regeneration and degeneration and inflammation that eventually result in replacement of myofiber by connective and adipose tissues. Emerging evidence suggests that gene expression and the activity of various MMPs are aberrantly regulated in muscle biopsies from DMD patients and in skeletal muscle of animal models of DMD. Moreover, a few studies employing genetic mouse models have revealed that different MMPs play distinct roles in disease progression in DMD. Modulation of the activity of MMPs improves myofiber regeneration and enhances the efficacy of transplantation and engraftment of muscle progenitor cells in dystrophic muscle in mouse models of DMD. Furthermore, recent reports also suggest that some MMPs especially MMP-9 can serve as a biomarker for diagnosis and prognosis of DMD. In this article, we provide a succinct overview of the regulation of various MMPs and their therapeutic importance in DMD.